2022
DOI: 10.1186/s13045-022-01266-8
|View full text |Cite
|
Sign up to set email alerts
|

Universal immunotherapeutic strategy for hepatocellular carcinoma with exosome vaccines that engage adaptive and innate immune responses

Abstract: Background Personalized immunotherapy utilizing cancer vaccines tailored to the tumors of individual patients holds promise for tumors with high genetic heterogeneity, potentially enabling eradication of the tumor in its entirety. Methods Here, we demonstrate a general strategy for biological nanovaccines that trigger tailored tumor-specific immune responses for hepatocellular carcinoma (HCC). Dendritic cell (DC)-derived exosomes (DEX) are painted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…Except for liver-, lung- and lymph node-specific delivery of RNA, the specific delivery of RNA to other organs after intravenous administration may enhance the utility of LNPs. In addition, extracellular vesicles (EVs) are an emerging platform for delivering siRNA, peptides or proteins [ 166 , 167 ]. EVs from red blood cells have been successfully used for intratumoral delivery of 5'-pppRNA as RIG-I agonist [ 168 ].…”
Section: In Vivo Delivery Of Rlr-activating Rna By Nanoparticles Extr...mentioning
confidence: 99%
“…Except for liver-, lung- and lymph node-specific delivery of RNA, the specific delivery of RNA to other organs after intravenous administration may enhance the utility of LNPs. In addition, extracellular vesicles (EVs) are an emerging platform for delivering siRNA, peptides or proteins [ 166 , 167 ]. EVs from red blood cells have been successfully used for intratumoral delivery of 5'-pppRNA as RIG-I agonist [ 168 ].…”
Section: In Vivo Delivery Of Rlr-activating Rna By Nanoparticles Extr...mentioning
confidence: 99%
“…Zhen et al reported that alpha-fetoprotein (AFP)-expressing Dex could induce potent antigen-specific immune responses in ectopic or orthotopic hepatocellular carcinoma (HCC) mice, improved the immune microenvironment of autologous tumors, and decrease the amount of immune stimulation cell and CD8+ CTL infiltration, levels of immunosuppressive cytokines and the number of Treg cells [ 149 ]. A recent study reported that Dex vaccine (DEX P&A2&N ) promoted the recruitment and activation of DCs in mice with liver cancer, thereby enhancing tumor-specific immune responses [ 150 ]. Studies have reported that DC cell-derived exosomes can cross the BBB to deliver RNAi to the brain and play a biological role, such as inhibiting tumor growth [ 151 ].…”
Section: Immune Cell-derived Exosomesmentioning
confidence: 99%
“…The results showed that the DC-based nanoparticle vaccine induced stronger IFN-γ-producing CTL-mediated cytotoxicity against the H22 cell line in vitro and exhibited better efficacy in suppressing tumor growth and prolonging survival in an ectopic allograft immunocompromised BALB/c mouse model than non-DC-based nanoparticle vaccine when combined with laser irradiation. Another study performed by Zuo et al evaluated the efficacy of a DC-derived exosome vaccine, which was prepared by co-conjugating an immortalized DC-line-derived exosome with an AFP-derived epitope AFP 212 , an HCC tumor-targeting peptide P47, and a functional domain of high mobility group nucleosome-binding protein 1 (HMGN1), an immunoadjuvant capable of promoting DC recruitment and activation, in treating HCC [ 61 ]. The results showed that the DC-derived exosome vaccine exhibited efficient efficacy in suppressing tumor growth and prolonging survival in both ectopic and orthotopic allograft immunocompetent C57BL/6 mouse models of the mouse HCC cell line Hepa1-6.…”
Section: Recent Preclinical Studies Regarding Dc-vaccine-based Immuno...mentioning
confidence: 99%